A randomised controlled trial of two methods of delivering nasal continuous positive airway pressure after extubation to infants weighing less than 1000 g: binasal (Hudson) versus single nasal prongs. Issue 2 (1st September 2001) - Davis, P; Davies, M; Faber, B
Abstract : OBJECTIVES: Primary: to determine whether nasal continuous positive airway pressure (CPAP) delivered through binasal prongs results in a greater proportion of extremely low birthweight infants being successfully extubated, after a period of intermittent positive pressure ventilation, than nasal CPAP delivered by a single nasal prong. Secondary: to evaluate the effect of mode of delivery of nasal CPAP after extubation on the need for endotracheal reintubation, weight gain, rates of feeding intolerance, sepsis, suspected sepsis, cranial ultrasound abnormalities, retinopathy of prematurity, chronic lung disease, and the duration of assisted ventilation and care in the tertiary neonatal unit. DESIGN AND SETTING: Randomised, controlled, clinical trial conducted at the neonatal intensive care unit of the Royal Women's Hospital, Melbourne, Australia. PATIENTS: Infants of birth weight less than 1000 g, ventilated, requiring < 50% oxygen and ventilator rate less than or equal to 20/minute, and considered by the clinical management team to be ready for extubation. INTERVENTION: Infants were randomly allocated to receive nasal CPAP delivered through binasal (Hudson) prongs or a single nasal prong. PRIMARY OUTCOME MEASURE: Failure of extubation as defined by the following criteria: ( a ) apnoea (more than one episode/hour over a six hour period or one episode requiring bag and mask ventilation); ( b ) absolute increase in oxygen requirement greater than 15% above that required before extubation; ( c ) respiratory acidosis (pH < 7.25 with PCO2  > 6.67 kPa). RESULTS: Ten of the 41 (24%) infants randomised to binasal prongs reached predetermined failure criteria compared with 26 of the 46 (57%) infants randomised to a single nasal prong (p = 0.005). Four of 17 (24%) infants of birth weight less than 800 g extubated to binasal prongs reached failure criteria compared with 14 of 16 (88%) extubated to a single nasal prong (p < 0.001). There were no significant differences in any of the secondary outcomes. CONCLUSIONS: For extremely low birthweight infants ventilated using an endotracheal tube, nasal CPAP delivered through binasal (Hudson) prongs is more effective in preventing failure of extubation than that delivered through a single nasal prong.